Modelling of oxygen transport through mixed ionic-electronic conducting (MIEC) ceramic-based membranes: An overview - Li, C.; Chew, J.; Mahmoud, A.; Liu, Shaomin; Sunarso, J. (Elsevier BV, 2018)
© 2018 Elsevier B.V. Oxygen demand has continuously increased given its indispensable role as a raw material in various large-scale industries and clean energy production. The present cryogenic and pressure swing adsorption (PSA) technologies are either energy intensive or are unable to produce very high purity oxygen. Mixed ionic-electronic conducting (MIEC) membrane is a promising alternative technology to produce high-purity oxygen above 700 °C. The main attraction of MIEC membranes lies in the fact that only oxygen can permeate through the membrane under the presence of oxygen partial pressure driving force that endows this technology 100% oxygen selectivity; giving 99.99% pure oxygen. The past two decades has observed rapid progress in the research and development of dense MIEC ceramic membrane technology, mainly along the materials science and engineering direction that seeks to maximise the oxygen permeation flux. Modelling serves as an essential aid to support the experimental progress, mainly to simulate and predict the experimental results and behaviour and to provide insights on the effect of design and operation variables. This review seeks to cover the advances in the oxygen permeation modelling studies over the past two decades by discussing the existing models, their applications in oxygen permeation process, and their limitations as well as the future direction.